Weed Management in Sorghum - Jason Ferrell; Gregory MacDonald; Barry Brecke; Pratap Devkota (EDIS, 2022)
This publication provides information on weed control options in sorghum. Written by J. A. Ferrell, G. E. MacDonald, B. J. Brecke, and P. Devkota, and published by the UF/IFAS Agronomy Department, revised January 2022.